The aesthetic and functional dimensions of the movement and trend in design industrial product (Journal of the College of Basic Education, 2023)
The direction is an essential element of the structural elements that share with other elementsTo shape the structure of the artwork in general and the industrial design in particular, as it comes overlappingAnd in combination with other elements that alienate each of them with symbolic meanings, including the direction from hereWe find that the designer's knowledge of these elements and their implications works to help him employ them in a serviceThe content of the industrial product From here came the research problem with the following questions1- What does the movement of shapes cause in the content of the industrial product?Is there a dialectical relationship between movement and direction?*- What are the attractive forces that affect the eye of the recipient?The research aimed to: reveal the aesthetic and functional dimensions of the mechanisms of operationMovement and direction in industrial product design.The research came out with several conclusions, the most important of which are:1- The idea of designing the industrial product for sample models can be embodied in the movement of lines withdifferent directionsAn industrial designer can include aesthetic features in a product through proper employmentFor design elements such as line, color, texture, size, direction, etc. and group them